Study of the Greenhouse Gas Emissions from Electric Buses Powered by Renewable Energy Sources in Poland - Piotr Folęga; Dorota Burchart (Energies)
The subject addressed in this article is the application of the life cycle assessment (LCA) method for studying the greenhouse gas emissions attributable to public bus transport. The article provides a discussion on the results of the authors’ in-house study on the greenhouse gas (GHG) emissions generated over the life cycle of the buses used in Poland’s public transport with the use of well-to-wheel (WTW) fuel life cycle analysis. The project started by adopting the methodology and assumptions for the research; next, the data required to perform the relevant analyses were collected and the greenhouse gas emissions attributable to the operation of buses equipped with both diesel fuel (DF) internal combustion engines and electric engines (BEVs) were assessed against real-life data using a selected Polish municipal transport company as an example in 2022. The study also included an assessment of GHG emissions from electric buses powered by renewable energy sources (RESs), using data from the chosen municipal transport company. For the RES fractions of 25%, 50%, and 75% in the energy mix, emission reductions of approx. 19%, 38%, and 57% have been achieved, respectively. For an energy mix entirely derived from RESs, the reduction in emissions comes to ca. 76% vis-à-vis Poland’s energy mix in 2022.